Tourism Destination Mapping Based on Tourism Characteristics and Carrying Capacity of Province in Indonesia - Masteriarsa, Muhammad Fikri; Riyanto (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2023)
The development of tourist destinations in Indonesia can encourage an increase in tourist visits and the length of stay of tourists while in tourist destinations. Tourism destination development needs to be in line with the characteristics of the tourism destinations they have. This study conducted a cluster analysis to map 34 provinces in Indonesia based on 13 aspects of tourism characteristics and carrying capacity. Mapping results formed four groups of tourist destinations with similar characteristics. Cluster-1 has the best average tourist carrying capacity, so it is classified as an advanced destination group consisting of West Java, Central Java, DI Yogyakarta, East Java, and Bali. Cluster-2 consists of DKI Jakarta and Riau Island, with two bad aspects, so they are classified as the revitalization of tourist destinations. Cluster-3 consists of North Sumatra, West Sumatra, Banten, West Nusa Tenggara, East Nusa Tenggara, West Kalimantan, East Kalimantan, South Kalimantan, South Sulawesi, North Sulawesi, and West Papua, which have poor performance in 6 aspects so that it is categorized as a developing tourism destination. Cluster-4 comprises 16 other provinces with poor performance in 9 elements, so it is classified as a pioneering tourist destination. Mapping results are compared with the policies of 10 priority tourism destinations (DPP) in Indonesia, and it is found that 3 DPPs (Bangka Belitung, Morotai-North Maluku, and Wakatobi-Southeast Sulawesi) are included in cluster-4 with the category of pioneer tourist destinations. Development of these 3 DPPs requires increased funding.